The development of a curriculum for a module in introductory Financial Accounting: an open distance learning approach - Jansen van Rensburg, Jacobus Stephanus (South African Journal of Higher Education, 2016)
This article looks into the processes and procedures that were followed and the research conducted towards the development of a curriculum for a new module in Introductory Financial Accounting at the University of South Africa, which is an open distance learning institution. Most of the aspects of curriculum development touched on will also be relevant for residential universities. The research method used to develop the curriculum was based on a thorough literature study of aspects of curriculum development. On the basis of this literature study, the curriculum development approach was devised and the determinants of curriculum development, that could have a special influence on the development of the new module, identified. The new module FAC1501 – Introductory Financial Accounting was introduced in the Diploma in Accounting Sciences in the School for Accounting Sciences’ new programme qualification mix (PQM). Because FAC1501 had no previous student body, it was necessary to do a thorough literature review of relevant statistical evidence gathered by other researchers regarding various aspects of this curriculum project and to adapt it where necessary. This, together with the determinants identified, provided guidelines for the selection and arrangement of learning content and preparation of the necessary tuition material. This article emphasises the fact that curriculum development is a never-ending team effort in the sense that the on-going process of monitoring and evaluating the curriculum together with possible changes in disciplinary knowledge, determines what factors should receive attention in the next cycle of curriculum development.